MODERNIZING THE INCOME STATEMENT. - Stans, Maurice H. (The Accounting Review, 1949)
Abstract In the corporate system, accounting has come of age. Accounting, the language of business, has grown in stature and importance and power in direct relation to the growth of industrial productivity. In the individual enterprise the measurement of production and of the division of the product occurs through the process of accounting for income. Its end-result is the income statement. Two factors make the job at this time more difficult than ever. The the public seems to have a basic lack of confidence in corporate accounting, brought about largely by a confusion of language and what has been aptly termed a growing "scatterization of methods." Being tied to a monetary unit, corporate accounting has limitations because it has no mechanism to adjust for changes in value of the monetary unit, In times such as the present when a seeming prosperity is interwoven with an obvious inflation, these factors have a cumulative effect. As the corporate system goes, so goes the economy. As the economy goes, so goes the political and social structure. Somehow the problem of economic balance must be solved or all of society will, in one way or another, either end in dictatorship or revert to the "pre-industry revolution" status of family self -sufficiency in which there are not problems of exchange or distribution.